Dos sentidos de la preposicion "πǫơs" en algunos pasajes de Platón - Peña y Gonzalo, Lorenzo (Estudios Humanísticos. Filología, 1986)
Dos sentidos de la preposicion "pros" en algunos pasajes de Platón